Distribution of pathotypes flora of wheat leaf rust pathogen (Puccinia recondita f. sp. tritici) in Nepal - S.K. NAYAR2, B.N. MAHTO1 and (Indian Phytopathology, 2002)
Pathotype distribution was assessed using leaf rust samples collected randomly at every 20 km or so, depending upon the geographical location and availability of the wheat crop. From 104 samples analysed, pathotype 77-2 (109 R 31-1) was found to bepredominant (72.11%) followed by 77-4 (125 R 31-1; 20.19%) and 77-5 (121 R 63-1; 7.69%). The pathotypes prevalent in different areas are described.